Numerical and Experimental Sensitivity Analysis for the Determination of Casting Parameter–Microstructure–Property Relations and Mechanical Properties of IN738LC in Investment Casting1. Issue 10 (10th June 2014) - Schmidt, Robin; Pusch, David; Voigt, Matthias; Vogeler, Konrad; Kulawinski, Dirk; Biermann, Horst; Holländer, Dirk; Gampe, Uwe; Tränkner, Mario; Leyens, Christoph; Gude, Maik; Hufenbach, Werner
<x xml:space="preserve">Abstract</x> The development of manufacturing processes for high‐performance investment casting components in turbomachinery is an iterative process, which takes a lot of development time for engineers and foundry occupation. The reduction of these expensive preliminary tests is possible by combining probabilistic methods with modern simulation tools for the numerical description of the casting and solidification processes. Starting from the deterministic simulation of the casting process, the casting and solidification parameters including their production tolerances are taken into account in the probabilistic simulation. Through a multi‐dimensional statistical analysis of the numerous parameters of the casting process and the achieved virtual casting results, the correlations between the process parameters and component quality can be worked out. Furthermore, a design of experiment (DoE) was performed with real castings to confirm the influence of the main parameters on the result quantities. Mechanical and microstructural characterizations of appropriate cast specimens allow a validation of the simulation results and the formulation of casting parameter–microstructure–property relations. The mechanical properties are studied by uniaxial hot tensile tests using standard and small‐scale specimens. Furthermore, the uniaxial fatigue behavior and the life times at elevated temperatures are investigated.